Progress in Synthesis of New Environmentally Friendly Insulation Gas Perfluoroisobutyronitrile (C4F7N). Issue 1 (September 2021) - Sun, Dongwei; Zhou, Yongyan; Tang, Nian; Zhang, Manjun; Li, Zhi
Abstract: The greenhouse effect potential value (GWP) of perfluoroisobutyronitrile (C4F7N) gas is 2400, the ozone depletion potential value (ODP) is 0, and the biological toxicity is low. The insulation strength of pure C4F7N gas at one atmosphere is about twice that of sulfur hexafluoride. As a substitute gas of sulfur hexafluoride, C4F7N gas has great potential in the application of medium and high voltage electrical equipment. In this paper, the research progress of C4F7N synthesis is reviewed, with emphasis on the advantages and disadvantages of the synthesis process, the possibility of scaling up the synthesis routes and the prospect of new synthesis methods of C4F7N are also discussed.